2003
DOI: 10.1590/s0103-84782003000500018
|View full text |Cite
|
Sign up to set email alerts
|

Peritonite infecciosa felina: 13 casos

Abstract: Numa pesquisa realizada em tecidos de 638 gatos necropsiados, foram encontrados 13 casos (2,03%) de peritonite infecciosa felina. Oito desses casos (61,53%) eram da forma efusiva ou úmida, e 5 apresentavam a forma seca ou não-efusiva da doença. A idade dos gatos afetados variou de 2 meses a 3 anos. Doze gatos (92,30%) eram de raças puras, cinco deles (38,47%) eram oriundos de ambientes onde havia mais de um gato e três eram provenientes de um mesmo gatil. A duração da doença clínica foi de 7 a 45 dias e os sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
1
0
0
9
Order By: Relevance
“…Adult males were the feline population most affected by infectious diseases (24.54%), with feline infectious peritonitis (FIP) as the most prevalent condition. This is in agreement with findings of previous studies, which demonstrated that a larger number of males, aged 3 months to 3 years (Oliveira et al 2003), unneutered (Rohrbach et al 2001) cats were affected by Coronavirus. This finding is again justified by the susceptibility of unneutered males to infectious diseases due to the search for in-estrus females and greater access to external environments, which culminate in greater contact with felines of unknown origin, facilitating the dissemination of infectious agents.…”
Section: Discussionsupporting
confidence: 94%
“…Adult males were the feline population most affected by infectious diseases (24.54%), with feline infectious peritonitis (FIP) as the most prevalent condition. This is in agreement with findings of previous studies, which demonstrated that a larger number of males, aged 3 months to 3 years (Oliveira et al 2003), unneutered (Rohrbach et al 2001) cats were affected by Coronavirus. This finding is again justified by the susceptibility of unneutered males to infectious diseases due to the search for in-estrus females and greater access to external environments, which culminate in greater contact with felines of unknown origin, facilitating the dissemination of infectious agents.…”
Section: Discussionsupporting
confidence: 94%
“…Estudos sobre causas de morte em pequenos animais ainda são escassos no Brasil (Trapp et al 2010) e os que estão disponíveis contemplam apenas cães (Bentubo et al 2007, Fighera et al 2008. Trabalhos sobre doenças em gatos no Rio Grande do Sul apenas foram realizados com base em doenças ou síndromes especificas (Wouters et al 1998, Souza et al 2002, Oliveira et al 2003, Ilha et al 2004, Headley 2005, Correa et al 2009, Andrade et al 2012, Togni et al 2013. Como os estudos foram realizados em diferentes épocas, direcionados apenas para uma doença ou síndrome específicas e em uma população variante, ainda encontram-se dificuldades em estabelecer a real prevalência das principais doenças que acarretam na morte ou na eutanásia de gatos na Região Central do Rio Grande do Sul.…”
Section: Introductionunclassified
“…Entre os anos de 2000 e 2013, 318 felinos foram examinados no LRD. Destes, 10 casos (3,14%) receberam o diagnóstico positivo para PIF, baseado nas lesões macro e microscópicas, que são consideradas diagnósticas (BARKER, 1993;DRECHSLER et al, 2011;KIPAR et al, 2005;OLIVEIRA et al, 2003). Segundo Gelberg (2013), 12% das mortes em felinos são associadas à PIF.…”
Section: Resultsunclassified
“…JARRETT, 1998), no entanto, o diagnóstico definitivo é realizado através da necropsia e histopatologia (BARKER, 1993;GELBERG, 2013). Os achados de necropsia e histopatológicos deste estudo estão de acordo com o que foi descrito por Barker (1993), Kipar et al (2005) e Oliveira et al (2003) para a doença e foram utilizados para a classificação na forma efusiva e seca.…”
Section: Resultsunclassified
See 1 more Smart Citation